Solubilization of hemicellulose and fermentable sugars from bagasse, stalks, and leaves of sweet sorghum - Martins, Rodrigo Pagano [UNESP]; Schmatz, Alison Andrei [UNESP]; de Freita, Lidyane Aline [UNESP]; Mutton, Marcia Justino Rossini [UNESP]; Brienzo, Michel [UNESP] (Elsevier, 2021)
Sweet sorghum is alternative biomass for ethanol and value-added molecules production due to its large production of juice and bagasse. The present study used sweet sorghum bagasse, stalk, and leaves to determine the influence of different treatments for hemicellulose solubilization (glucuronoarabinonoxylan), xylose and glucose production. Hemicellulose solubilization was performed using alkaline methods with 6% and 10 % (w/v) H2O2, 10 % (w/w) NaOH, and 10 % (w/w) KOH, and xylose produced with 1% (w/w) H2SO4. Untreated bagasse, stalks, and leaves of sweet sorghum presented a cellulose proportion of 43.58 %, 42.23 %, and 35.09 %; the hemicellulose proportion was 24.51 %, 22.14 %, and 20.51 %, and of lignin was 26.22 %, 20.92 %, and 19.93 %, successively. The hemicellulose solubilization yield varied from 17.79 % with stalk pretreatment with 6% H2O2 and 96.8 % with 10 % NaOH. Enzymatic hydrolysis resulted in yield greater than 90 % for all biomasses pretreated with 10 % H2O2 and above 80 % for biomasses pretreated with 10 % KOH. Considering the solubilization yield and the chemical composition, the hemicellulose from the bagasse and stalks with 10 % NaOH was the most effective in the solubilization. This condition is also an advantage for enzymatic hydrolysis purposes of the pretreated materials. However, it is important to observe that hydrogen peroxide resulted in a high hemicellulose yield with colorless, requiring lower washing step.
Keywords: Biomass; Enzymatic hydrolysis; Glucose; Pretreatment; Sorghum bicolor L. Moench; Xylose